Preparação para a performance de uma obra escrita para sexteto: suíte para tuba do compositor Marcelo Vilor - Silva, Gilvan Pereira da (2023)
The main focus of this research work is to present the interpretative preparation of the work “Suite para Tuba” by the composer from Paraiba, Marcelo de Araújo Vilor, which was written especially for this master's degree. It was structured from Brazilian musical rhythms and genres that permeate the compositional universe of this musician who has been standing out in our musical scene through his writing for brass instruments. We are exposing here a form of collective interpretation based on the musical work of Sexteto Potiguar, a brass quintet plus percussion that is a permanent group of the UFRN School of Music. This interpretative work has as its starting point the individual study of the group's instrumentalists, showing a little of their daily technical preparation, which will affect in a very effective way the final result of their performance. Starting from the individualized personal study, the ensemble proceeds through its rehearsals, promoting quite democratic discussions, where it works on passages considered difficult within the play. Then, the group's musicians choose the best way to interpret them, always according to their vision and experience. These procedures, which are carried out systematically and depart from the individual to the collective, reveal the sound identity of the group that has been standing out for a long time through its interpretive work of Brazilian musical genres, notably the Northeastern ones. This dissertation also has a historical part that addresses issues related to brass instruments, showing a little of their performance from the Middle Ages to the 19th century, when the tuba, pistons and rotors were invented, events that changed to always the context and the technical possibilities that involve these instruments. We also approach issues related to the emergence of the "brass quintet" formation, showing some national and international groups that from this configuration became famous and left a great contribution to our area. In addition, we consider it important to weave more detailed information about the composer Marcelo Vilor and the Sexteto Potiguar, showing a little of their stories through their paths within the musical environment, as they already stand out through an established and consolidated partnership for a long time. In this way, we leave as a final product of this research, in addition to the dissertation itself, a recording of the work, which is configured as the sound result of this work, which intends to transmit to the readers the musical identity of the Sexteto Potiguar.